Pemikiran Muhammad Shahrur Tentang Pakaian Perempuan Dan Hubungannya Dengan Maqasid Al-Shari’ah: Muhammad Shahrur's Thoughts On Women's Clothing And Its Relationship To Maqasid Al-Shari'ah - A. Halil Thahir (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2009)
The issue of clothing fashion, it turns out, is not only important from an Islamic perspective, but also has a connection to the personal issues of the wearer. It is in this context that Muhammad Shahrur attempts to examine women's clothing based on three foundations, namely: methodological, historical, and normative aspects. From his exploration of these three foundations, Shahrur discovered the concept of women's clothing that is “ideal and should be” according to him. According to Shahrur, the command to dress is not a matter of halal or haram, but is a ta'limat (teaching) on how a person can behave properly in accordance with the demands of the situation and conditions. A person can “ijtihad” (exercise independent reasoning) to determine the style and which parts of the body to cover as long as they do not violate the minimum and maximum limits. Thus, the minimum limit (al-hadd al-adna) of women's clothing is daruriyyah, something that must be done when interacting with people other than mahrams, while covering body parts between the minimum and maximum limits falls under the category of hajiyyat, something that is “necessary” to cover, because if not, she will feel uncomfortable interacting with others and it will not diminish her human dignity. Persoalan mode pakaian, ternyata tidak hanya menemukan urgensinya dalam perspektif Islam, tetapi memliki keterkaitan pula dengan persoalan pribadi pemakainya. Dalam konteks inilah hadir Muhammad Shahrur yang mencoba mengkaji pakaian perempuan dengan berpijak pada tiga landasan, yaitu: aspek metodologis, historis, dan normatif. Dari hasil penjejakannya atas tiga landasan itu, Shahrur menemukan konsep pakaian perempuan yang